Motivations and Behavioral Patterns of Sexual Harassment Perpetrators: A Qualitative Study in Bandung City, Indonesia - Keysha Januarita Anandita Simbolon; Afianti Sulastri; Irma Darmawati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Sexual harassment is a persistent social and public health problem, particularly in urban contexts where complex social interactions and power relations are prevalent. While existing research has largely centered on victims’ experiences, limited attention has been directed toward understanding the motivations and behavioral patterns of perpetrators, especially within the Indonesian sociocultural context. Objective: This study aimed to explore the motivations, behavioral processes, and cognitive patterns underlying sexual harassment perpetration based on perpetrators’ own perspectives in Bandung City, Indonesia. Methods: A qualitative study employing a phenomenological approach was conducted among individuals convicted of sexual harassment and currently serving sentences in a correctional facility in Bandung City. Data were collected through in-depth, semi-structured interviews. Reflexive thematic analysis was used to identify recurring themes related to motivations, behavioral development, rationalization strategies, and moral awareness. Results: Six interrelated themes emerged from the analysis. Sexual harassment behavior was driven by internal psychological factors, including sexual desire, curiosity, emotional dysregulation, and low self-control. Social and cultural environments that normalized harassment reinforced these behaviors. Power imbalances between perpetrators and victims facilitated domination and reduced resistance. Harassing behaviors typically developed gradually, starting with minor boundary violations and escalating over time. Perpetrators employed cognitive rationalization and strategic risk management to justify their actions and avoid detection. Moral awareness and remorse varied and often emerged only after legal consequences were experienced. Conclusion: Sexual harassment perpetration is shaped by a complex interaction of individual, social, and structural factors. Understanding perpetrators’ motivations and behavioral patterns is crucial for informing comprehensive prevention strategies, rehabilitation programs, and policy development. Integrating perpetrator-focused education on consent, emotional regulation, and ethical behavior alongside victim-centered approaches is essential to effectively reduce sexual harassment